Foam-mat dried banana (Musa Cavendish) powder-development, packaging & storage studies - Lim, Ruby B.; Alabastro, Estrella F. (1977.)
This study was conducted with the objective of coming up with a powdered product using banana rejects of the cavendish variety as raw material and foam-mat drying as the method of dehydration. It also aimed to study suitable packaging materials for the product and to determine the shelf-life of the packaged product under a storage condition of 81% R.H. and 28°C. The first phase if the study was the standardization of a procedure for the production of foam-mat dried banana powder. The standard procedure developed is as follows. Puree fully ripe bananas together with 1000 ppm sulfite. Add 2.0% (based on solids weight of puree) egg albumin powder to the puree and whip the mixture for five minutes. Extrude the resulting foam on to aluminum screen trays and dry in a cabinet dryer at 16°F for 1 1/2 hours and then at 140°F for 30 minutes. Scrape the dried strips from the trays, pulverize and pack in water vapor proof materials. The second phase studied packaging requirements of the product. its sorption isotherm was determined by using the weight equilibrium method. The critical moisture content of the product was determined by storing several packages of the product at accelerated humidity conditions of 100% R.H. From the results of the periodic evaluation made on the product, the critical moisture content was determined to be 11.9%. The maximum allowable water vapor transmission rate (WVTR) was computed to be 0.776% g/m^2/day at 90% R.H. gradient and a temperature of 28°-30°C for a package with dimensions of 12 cm x 16 cm and containing 50 grams of the powder. The shelf life of the product was set at 180 days under a storage condition of 81% R.H. and 28°C. Therefore, packaging films were laminates of Saran/Polyethylyene, Foil/Polyethylene, and Cellophane/Polyethylene/Foil/Polyethylene. The adequacy of these as packaging materials for foam-mat dried banana powder was tested by the half-value period method of shelf life determination. Results of the test showed that the product is expected to have a shelf life of 1040 days when packed in Cellophane/Polyethylene/Foil/Polyethylene. With Foil/Polyethylene as packaging material, shelf life was determined to be 270 days and when packed in Saran/Polyethylene, shelf life of the product was only 120 days. With the desired shelf life set at 180 days, results of the shelf life test point to Foil?Polyethylene as the best packaging material for the product because it is much cheaper (P8.50/m^2) compared to Cellophane/Polyethylene/Foil/Polyethylene (P15.00 m^2) and yet provides adequate protection to the product.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Bananas; Banana -- Processing